Penerapan PENERAPAN SISTEM INFORMASI MANAJEMEN NIKAH (SIMKAH) WEB DI KANTOR URUSAN AGAMA (KUA) LABUHAN DELI DALAM PELAYANAN ADMINISTRASI KARTU NIKAH DIGITAL - Nazmi Agustian (PKM-P, 2022)
Abstract – This paper describes the application of the Web Marriage Management Information System (SIMKAH) at the Labuhan Deli Religious Affairs Office in the administration of Digital Marriage Cards. Indonesia is currently intensively carrying out a digitalization revolution in every aspect of people's lives. Of course this also applies to the Ministry of Religion of the Republic of Indonesia. This system is useful for collecting all marriage data from every KUA in Indonesia online and offline. This Marriage Card is proof of additional documents from the KUA which has a digital-based barcode, if it is scanned by a married couple, it will display complete information data regarding marital status, names, dates, photos of the bride and groom, and the place of the wedding. The results showed that the implementation of SIMKAH in the Digital Marriage Card service at KUA Labuhan Deli went well and effectively. The implementation of SIMKAH has been started since 2014, but has not been emphasized as much as it is now. In 2015, SIMKAH has begun to be used publicly and effectively and in 2018 was able to print Digital Marriage Cards so that the bride and groom get two documents after carrying out the marriage contract, namely the marriage book and marriage card. The application of programs in this digital era, of course, is very beneficial for the benefit of the community.